Building a Conceptual Framework to Culturally Adapt Health Promotion and Prevention Programs at the Deep Structural Level. Issue 4 (July 2014) - Wang-Schweig, Meme; Kviz, Frederick J.; Altfeld, Susan J.; Miller, Arlene M.; Miller, Brenda A.
The debate on the effectiveness and merit for the amount of time, effort, and resources to culturally adapt health promotion and prevention programs continues. This may be due, in large part, to the lack of theory in commonly used methods to match programmatic content and delivery to the culture of a population, particularly at the deep structural level. This paper asserts that prior to the cultural adaptation of prevention programs, it is necessary to first develop a conceptual framework. We propose a multiphase approach to address key challenges in the science of cultural adaptation by first identifying and exploring relevant cultural factors that may affect the targeted health-related behavior prior to proceeding through steps of a stage model. The first phase involves developing an underlying conceptual framework that integrates cultural factors to ground this process. The second phase employs the different steps of a stage model. For Phase I of our approach, we offer four key steps and use our research study as an example of how these steps were applied to build a framework for the cultural adaptation of a family-based intervention to prevent adolescent alcohol use, Guiding Good Choices (GGC), to Chinese American families. We then provide a summary of the preliminary evidence from a few key relationships that were tested among our sample with the greater purpose of discussing how these findings might be used to culturally adapt GGC.